2018
DOI: 10.4103/aca.aca_16_18
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of continuous thoracic epidural analgesia with bilateral erector spinae plane block for perioperative pain management in cardiac surgery

Abstract: Objective:Continuous thoracic epidural analgesia (TEA) is compared with erector spinae plane (ESP) block for the perioperative pain management in patients undergoing cardiac surgery for the quality of analgesia, incentive spirometry, ventilator duration, and intensive care unit (ICU) duration.Methodology:A prospective, randomized comparative clinical study was conducted. A total of 50 patients were enrolled, who were randomized to either Group A: TEA (n = 25) or Group B: ESP block (n = 25). Visual analog scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(67 citation statements)
references
References 24 publications
3
62
0
2
Order By: Relevance
“…The ESP block is a fascial plane block, which is performed between the transverse processes and erector spinae muscles, with a moderate level of difficulty, and can provide adequate analgesia through multiple dermatomes by cephalocaudal spread, as reported by Ivanusic et al [ 8 ]. Although this study reported no spread of dye to the ventral rami, several (published) studies have provided evidence, supporting the idea that anterior spread of local anesthetic provides visceral fiber blockade, explaining its use in thoracic, cardiac and abdominal surgery [ 9 13 ]. A recent case report described Harlequin syndrome after the ESP block, which is clearly consistent with the anterior spread of local anesthetic solution responsible for sympathetic fiber chain blockade [ 14 ].…”
Section: Discussionsupporting
confidence: 70%
“…The ESP block is a fascial plane block, which is performed between the transverse processes and erector spinae muscles, with a moderate level of difficulty, and can provide adequate analgesia through multiple dermatomes by cephalocaudal spread, as reported by Ivanusic et al [ 8 ]. Although this study reported no spread of dye to the ventral rami, several (published) studies have provided evidence, supporting the idea that anterior spread of local anesthetic provides visceral fiber blockade, explaining its use in thoracic, cardiac and abdominal surgery [ 9 13 ]. A recent case report described Harlequin syndrome after the ESP block, which is clearly consistent with the anterior spread of local anesthetic solution responsible for sympathetic fiber chain blockade [ 14 ].…”
Section: Discussionsupporting
confidence: 70%
“…compared ESP block with continuous catheter infusion and TEA. [ 30 ] This study found both blocks to be equally efficacious in the initial 12 h after extubation. However, VAS scores in TEA group were found significantly higher at 24, 36, and 48 h, but the mean values in both groups nevertheless remained in the mild pain range (VAS <4).…”
Section: Discussionmentioning
confidence: 81%
“…Studies are ongoing to show their non-inferiority to neuraxial anesthesia. 17,18 As our case illustrates, successful neuraxial anesthesia may provide effective analgesia without the need for systemic opioids so that maintenance therapy can be sustained. Even with an effective epidural placement, patients may require an increase in concentration of local anesthesia for excellent pain control due to resistance to local anesthetic agents in opioid tolerant patients.…”
Section: Discussionmentioning
confidence: 94%